x = y^2 - y
y^2 - y + 1 = x + 1
(y-1)^2 = x + 1
y -1 = sqrt (x+1)
y = 1 + sqrt (x+1)
Find a formula for the inverse of the function.
y=x^2-x, x>=(greater than or equal to) 1/2
Please give me a step by step explanation. I think my algebra is wrong... Ty
4 answers
noticed an error from line 2 to line 3
y^2 - y = x
y^2 - y + 1/4 = x + 1/4
(y - 1/2)^2 =(4x+1)/4
y - 1/2 = ±√(4x+1)/2
y = 1/2 ± √(4x+1)/2
= (1 ± √(4x+1) )/2 , x ≥ -1/4
y^2 - y = x
y^2 - y + 1/4 = x + 1/4
(y - 1/2)^2 =(4x+1)/4
y - 1/2 = ±√(4x+1)/2
y = 1/2 ± √(4x+1)/2
= (1 ± √(4x+1) )/2 , x ≥ -1/4
Whoops !
I don't understand. Why are you adding 1/4? to both sides? I don't see how you are getting a quadratic formula from this. More importantly, thank you guys for the help!